PENGARUH ROA TERHADAP FDR PADA LAPORAN KEUANGAN BANK MUAMALAT TAHUN 2018 - 2022 - Trisna Amarsya, Emilia; Firmansyah, Joni; Sundari, Ria; Wati, Dera; Nurhafiani, Nurhafiani (COSMOS : Jurnal Ilmu Pendidikan, Ekonomi dan Teknologi, 2024)
In Indonesia, the bank that provides Islamic banking services is Bank Muamalat Indonesia which was established in 1991. The use of financial ratios is the most common and simple method, which is why it is widely used to measure bank performance. This study aims to analyze the effect of Return on Assets (ROA) on the Funding Deposit Ratio (FDR) in Bank Muamalat's financial statements for 2018-2022. The type of research used in this study is quantitative data called numerical data. The data analysis techniques used in this study are descriptive statistics, classical assumption tests which include normality tests, multicollinearity tests, heteroscedasticity tests and autocorrelation tests to determine the accuracy of the model and hypothesis tests are also carried out which include F test (Simultaneous Test) and T test (Partial Test). The results of this study show that regression analysis shows a significant relationship between ROA and FDR, where the performance of bank assets reflected in ROA, can affect the level of dependence of banks on third-party funds, which is reflected in FDR. So that the value of the determination coefficient (R^2) of 0.212 or 21.2% shows that the ROA variable is able to explain about 21.2% of the variation in the FDR rate, while the remaining 78.8% is influenced by other factors that were not studied in this study. Although ROA is able to explain some of the variations in FDR levels, other factors also influence the relationship between ROA and FDR. Recommendations for further research include expanding the scope of variables, consideration of external factors that affect the relationship between ROA and FDR, and a more in-depth analysis to understand the dynamics of the relationship between bank asset performance and the level of dependence of banks on third-party funds.